Misdirection of endosomal trafficking mediated by herpes simplex virus–encoded glycoprotein B. Issue 4 (24th January 2017) - Niazy, Naima; Temme, Sebastian; Bocuk, Derya; Giesen, Carmen; König, Angelika; Temme, Nadine; Ziegfeld, Angelique; Gregers, Tone F.; Bakke, Oddmund; Lang, Thorsten; Eis‐Hübinger, Anna M.; Koch, Norbert
Abstract : Herpes simplex virus (HSV)–encoded glycoprotein B (gB) is the most abundant protein in the viral envelope and promotes fusion of the virus with the cellular membrane. In the present study, we found that gB impacts on the major histocompatibility complex (MHC)‐II pathway of antigen presentation by fostering homotypic fusion of early endosomes and trapping MHC‐II molecules in these altered endosomes. By using an overexpression approach, we demonstrated that transient expression of gB induces giant vesicles of early endosomal origin, which contained Rab5, early endosomal antigen 1 (EEA1), and large amounts of MHC‐II molecules [human leukocyte antigen (HLA)‐DR, and HLA‐DM], but no CD63. In HSV‐1–infected and stably transfected cell lines that expressed lower amounts of gB, giant endosomes were not observed, but strongly increased amounts of HLA‐DR and HLA‐DM were found in EEA1 + early endosomes. We used these giant vesicles as a model system and revealed that gB interacts with Rab5 and EEA1, and that gB‐induced homotypic fusion of early endosomes to giant endosomes requires phosphatidylinositol 3‐phosphate, the activity of soluble N‐ethylmaleimide‐sensitive factor attachment protein receptors, and the cytosolic gB sequence 889 YTQVPN 894 . We conclude that gB expression alters trafficking of molecules of the HLA‐II processing pathway, which leads to increased retention of MHC‐II molecules in early endosomal compartments, thereby intercepting antigen presentation. —Niazy, N., Temme, S., Bocuk, D., Giesen, C., König, A., Temme, N., Ziegfeld, A., Gregers, T. F., Bakke, O., Lang, T., Eis‐Hübinger, A. M., Koch, N. Misdirection of endosomal trafficking mediated by herpes simplex virus–encoded glycoprotein B. FASEB J . 31, 1650–1667 (2017) www.fasebj.org